Creative courage : leveraging imagination, collaboration, and innovation to create success beyond your wildest dreams - Altidor, Welby, 1973- (Hoboken, New Jersey : Wiley, 2017)
'Achieve more, do more, create more with the power of creative courage Creative Courage challenges you to step outside of your comfort zone and truly make an impact. Set aside the same old routine and break the status quo$1 (Bbecause you can only rise to new heights if you first smash the ceiling. Written by the former Executive Creative Director of Creations at Cirque du Soleil, this book shows you how to step up your game, flex your creativity, and make big things happen. Whether you work independently or as part of a team, whether you're self-employed or part of an organization, and even if you think creativity isn't a part of the work that you do$1 (Bthis book gives you the perspective, courage, and kick start you need to think differently about the things you do every day. Creative courage is more than a strategy, it's a way of life. It opens your mind$1 (Band the minds of those around you$1 (Bto new approaches, new ideas, and new schools of thought that can revolutionize the way you work. This book invites you to experience the freedom and power at the intersection of courage and creativity so you can finally: Foster a more collaborative culture Bring depth and meaning to every project Turn challenge into opportunity Create work that matters The value of creative thinking extends far beyond the arts, but the work it allows you to produce has the power to touch like great art can. You gain the ability to make a more profound impact, and you inspire and motivate others to do the same; you become a catalyst for bigger, better things, driven by the enormous potential of the free-thinking mind. Creative Courage helps you break out of the box and start making things happen today'--s
'This book challenges you to step outside of your comfort zone and truly make an impact. Set aside the same old routine and break the status quo--because you can only rise to new heights if you first smash the ceiling. Written by the former Executive Creative Director of Creations at Cirque du Soleil, this book shows you how to step up your game, flex your creativity, and make big things happen. Whether you work independently or as part of a team, whether you're self-employed or part of an organization, and even if you think creativity isn't a part of the work that you do--this book gives you the perspective, courage, and kick start you need to think differently about the things you do every day'--
Machine generated contents note: INTRODUCTION: CREATIVE COURAGE CHAPTER 1 - THE CENTRAL PROBLEM AFFECTING WORK: THE WAR ON IMAGINATION, AND HOW I LOST MY CREATIVE COURAGE. CHAPTER 2 - CARING FIRST: RESPECT IS NOT THE FIRST STEP WHEN DISENGAGEMENT IS THE STATUS QUO. CHAPTER 3 - SECURING SAFETY: NO SAFETY, NO TRUST. CHAPTER 4 - FOSTERING TRUST: THE NATURAL STATE OF SILOS CHAPTER 5 - PLAYING WITH DANGER: WHEN THE STAKES ARE SO HIGH THAT WE JUST WANT TO PLAY SAFE CHAPTER 6 - DREAMING: SPREADSHEETS DON'T DREAM CHAPTER 7 - BREAKTHROUGH & DISCOVER: THE NEGLECTED AREA OF HUMAN EMOTIONS AND THE EDGE OF THE FUTURE CHAPTER 8 - GROW: CAN YOU MAKE THE LOGO 30% BIGGER? WHAT IF IT'S NOT ABOUT THE LOGO? CHAPTER 9 - STARTING TO DANCE: IT'S NEVER TOO LATE TO START DANCING CONCLUSION: 50% MORE.
Includes bibliographical references and index.
Keywords: Altidor, Welby, -- 1973-; Cirque du Soleil; Creative ability in business; Leadership; Success in business